For the given functions, we will find the first derivative of each function
Note:
a, and b are constants
y, f, and g are functions
2) y = (a+bf)/g
We will use the quotient rule to find y' as follows:
![y^(\prime)=(g*b(df)/(dx)-(a+bf)(dg)/(dx))/(g^2)](https://img.qammunity.org/2023/formulas/mathematics/college/f58og4cqjkxdci8qdcjecsc3q47t4acaa0.png)
=============================================================
3) y = (x+f)/g
We will use the quotient rule to find y' as follows:
![y^(\prime)=(g(1+(df)/(dx))-(x+f)(dg)/(dx))/(g^2)](https://img.qammunity.org/2023/formulas/mathematics/college/j7yek9n0fahnrmmy1w6ghhz55kdcovb44i.png)
==========================================================
4) y = (x+f)³
We will use the exponent rule to find the derivative as follows:
![y^(\prime)=3(x+f)^2(1+(df)/(dx))](https://img.qammunity.org/2023/formulas/mathematics/college/wujfd7ohitl5kjkwxdf1zqss9ja6hozwe4.png)
===========================================================
5) y = ax² + bg² + f
so, y' will be as follows:
![y^(\prime)=2ax+2bg(dg)/(dx)+(df)/(dx)](https://img.qammunity.org/2023/formulas/mathematics/college/cf0cf19h4jpvv4nt62jb7k6n6g0yvusgfd.png)
==========================================================